Money for novelty: The role of venture capital investments for innovation in young technology-based firms - Diana Heger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper examines the role of venture capital on a firm's innovation activities by using a data set of German technology-based firms founded between 1996 and 2005. Innovation is proxied by patent counts and an index of innovativeness which reflects the degree to which a young firm has developed new technologies based on its own or external resources. The results show that VC financing has a positive impact on both patenting and innovativeness, even if we account for endogeneity of VC financing.
urn:nbn:de:bsz:180-madoc-347922
Keywords: O31; G24; C31; C35; L20; 330; innovation; venture capital; young technology-based firms; discrete choice methods; count data models; endogeneity